Identification of Genetic Determinants Responsible for the Rapid Immunosuppressive Activity and the Low Leukemogenic Potential of a Variant of Friend Leukemia Virus, FIS-2 - Dai, Hong Yan (American Society for Microbiology, 1998)
An immunosuppressive variant of Friend murine leukemia virus (F-MuLV), FIS-2, induces suppression of the primary antibody response against sheep erythrocytes (SRBC) in adult NMRI mice more efficiently than the prototype F-MuLV clone 57 (cl.57). It is, however, less potent than F-MuLV cl.57 in inducing erythroleukemia upon inoculation into newborn NMRI mice. Nucleotide sequence analysis shows a high degree of homology between the two viruses. Single point mutations are scattered over both the gag and the env encoding regions. The most notable mutations are the deletion of one direct repeat and a few single point mutations occurring in the binding sites for cellular transcriptional factors in the FIS-2 long terminal repeat region (LTR). To define the genetic determinants responsible for the pathogenic properties of FIS-2, we constructed six chimeras between FIS-2 and F-MuLV cl.57. Adult mice were infected with the chimeras, and their primary antibody responses against SRBC were investigated. The results showed that the fragment encompassing the FIS-2 env encoding region SU is responsible for the increased immunosuppressive activity in adult mice. A leukemogenicity assay was also performed by infecting newborn mice with the chimeras. Consistent with the previous studies, it showed that the deletion of one direct repeat in the FIS-2 LTR is responsible for the long latent period of erythroleukemia induced by FIS-2 in newborn-inoculated mice. However, studies of cell type-specific transcriptional activities of FIS-2 and F-MuLV cl.57 LTRs using LTR-chloramphenicol acetyltransferase constructs showed that the deletion of one direct repeat does not reduce the transcriptional activity of the FIS-2 LTR. The activity is either comparable to or higher than the transcriptional activity of the F-MuLV cl.57 LTR in the different cell lines that we used, even in an erythroleukemia cell line. It seems that the high transcriptional strength of the FIS-2 LTR is not sufficient to give FIS-2 a high leukemogenic effect. This suggestion is inconsistent with the previous suggestion that the transcriptional strength of an LTR in a given cell type is correlated with the leukemogenic potential in the corresponding tissue. In other words, these data indicate that the direct repeats in the F-MuLV LTR may play other roles besides transcriptional enhancer in the leukemogenesis of F-MuLV.